Nanoadhesion of Staphylococcus aureus onto Titanium Implant Surfaces. (August 2015) - Aguayo, S.; Donos, N.; Spratt, D.; Bozec, L.
Adhesion of bacteria to dental implant surfaces is the critical initial step in the process of biofilm colonization; however, the specific nanoadhesive interactions occurring during the first contact between bacterial cells and biomaterial substrates remain poorly understood. In this report, we utilize single-cell force spectroscopy to characterize the dynamics of the initial interaction between living Staphylococcus aureus cells and machined titanium surfaces at the nanoscale. Values for maximum adhesion force were found to increase from 0-s (–0.27 ± 0.30 nN) to 60-s (–9.15 ± 0.78 nN) surface delays, with similar results observed for total adhesion work (7.39 ± 2.38 and 988.06 ± 117.08 aJ, respectively). Single unbinding events observed at higher surface delays were modeled according to the wormlike chain model, obtaining molecular contour-length predictions of 314.06 ± 9.27 nm. Average single-bond rupture forces of −0.95 ± 0.04 nN were observed at increased contact times. Short- and long-range force components of bacterial adhesion were obtained by Poisson analysis of single unbinding event peaks, yielding values of −0.75 ± 0.04 and −0.58 ± 0.15 nN, respectively. Addition of 2-mg/mL chlorhexidine to the buffer solution resulted in the inhibition of specific adhesive events but an increased overall adhesion force and work. These results suggest that initial attachment of S. aureus to smooth titanium is mostly mediated by short-range attractive forces observed at higher surface delays.